BUILDING ON BARRON: THE PROSPECTS FOR THE STUDY OF PRE-ISLAMIC ANTIQUITY IN THE 21 CENTURY. - DAVIES, JOHN (Bulletin of the Institute of Classical Studies, 2010)
The article offers the author's insights concerning the pre-Islamic antiquity in the 21st century and John Penrose Barron. He mentions that pre-Islamic has been a major expansion, which changed first the political and then the cultural map. Moreover, he mentions six optimistic assumptions including that there will no global pandemic on the lethal scale of the Black Death and the effects of global warming and climate change will not render intellectual and scholarly life impossible.